Design of a machine for the removal process of starchy green corn kernels: https://doi.org/10.15332/24222399.2947 (Revista Cientifica Ingenio Magno, 2024)
The purpose of this article is to expose or show the design of a machine for the removal of green corn kernels with the objective of improving the activity of the shelling process of starchy green corn. To achieve this objective, recognized methods in the field of engineering, the creation of concepts and the compilation of data on the mechanical properties of each component of the machine and/or the specific materials to be removed have been applied. Multiple models of previously generated ideas are highlighted, which have been submitted to evaluation criteria, with a view to developing a patentable and viable solution
Keywords: Shelling; removal; green corn; design